Creation a Blockchain-based Product Qualification System for E-Marketplace using Practical Byzantine Fault Tolerance Algorithm - Nizuar, Irvan; Handayani, Linda; Sudiro, Sunny Arief (STKIP PGRI Tulungagung, 2023)
An indicator of e-marketplace effectiveness is to facilitate transparent transactions between sellers and buyers by offering good products and adequate infrastructure to handle system requirements. A good product must be in accordance with the product qualification which consists of the classification of feasibility or not, and the benefits of the product. However, this often has problems including those caused by frequent problematic system conditions, non-transparent product qualifications, undistributed data, human error until data security. The researcher proposes the creation of a product qualification system for e-marketplace using blockchain technology. The product qualification system consists of data verification and validation carried out by stakeholders involved in the decentralized network. Transactions that have been executed and validated will be stored in the distributed ledger. The focus of this research is the implementation of blockchain that is allowed to use the PBFT algorithm on product qualification records in the e-marketplace. The purpose of this research is to create a blockchain-based product qualification system for e-marketplace that is transparent and immutable and the successful performance of the system in information storage and management security. The results show the creation of a web-based apps product qualification system that implements a blockchain using Hyperledger Fabric and the performance obtained through system testing and data validation testing.